How Do Start-up Characteristics and Innovation Practices Influence Share Value? An Empirical Examination - Anjhu Richer Natal Ebenezer Situmorang; Mochammad Fahlevi; Yeni Ariesa (Universitas Mercu Buana, 2023)
Start-up ecosystems, with their inherent dynamism and potential for innovation, have grown significantly in recent years. However, understanding the factors that influence their share value remains an intricate task. This research aims to elucidate the direct and indirect impacts of start-up attributes - assets, capital, and employees - and their innovative practices on the share value of these burgeoning enterprises. Using regression analysis on data collected from start-ups operating between 2019 and 2022, this study uncovers several critical insights. The assets, capital, and number of employees were found to have a significant influence on the level of innovation within the start-up. Yet, surprisingly, these factors, along with innovation itself, did not exert a direct influence on the start-up shares. However, an indirect effect was noticed, with assets and capital influencing shares when mediated by innovation. No such indirect effect was discerned with the number of employees. This study enriches the existing literature by providing a nuanced perspective on the interconnectedness of start-up characteristics, innovation, and share value. Moreover, it presents vital insights to investors and start-up decision-makers by underscoring the essential role of innovation in enhancing share value. For future research, exploration of other potential mediators and examination of these relationships across diverse start-up contexts is recommended to develop a more comprehensive understanding.